The Effect of Good Corporate Governance Implementation and Company Size on Sustainability Report - Muhammad Habibie (Journal on Education, 2023)
This study aims to determine the effect of Good Corporate Governance, Company Size on the Disclosure of Sustainability Reports in Companies Listed on the Indonesia Stock Exchange in 2020. The population of this study were companies listed on the Indonesia Stock Exchange in 2020 that issued a Sustainability Report, namely 107 companies that were taken. using purposive sampling method. Data analysis techniques are descriptive statistics, classical assumption test, multiple linear regression analysis, hypothesis testing and coefficient of determination. The results of this study indicate that Good Corporate Governance with the board of commissioners partially positive and significant effect on the Sustainability Report, with the board of directors partially negative and significant effect on the Sustainability Report, the audit committee and Company Size partially positive and insignificant effect on the Sustainability Report.